Audit of Partial and Complete Hydatidiform Moles in Tertiary Care Hospital JPMC, Karachi - Zumrud Momin, Noshaba Rahat, Humera Shazad, Mohammad Anwar, Amtul Qudos, Marvi Umair (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study aims to investigate the clinical presentation, frequency and histopathology of hydatidiform mole, as well as to determine the clinical significance of such histopathological examination. Material and method: This was a retrospective study undertaken at the Department of Pathology Bmsi Jpmc Karachi from January 1st, 2016 to November 31st, 2021.All molar pregnancy cases were thoroughly examined, taking into account their age, gestational age, signs and symptoms, clinical diagnosis where available and histopathology. Results: Total 73 cases of hydatidiform moles were obtained during study period. There were 64.3% partial hydatidiform moles and 35.6 % complete moles. The majority of the patients were between the ages of 21 and 35 years. Bleeding per vaginum was the most prevalent presenting symptom. The period of gestation in majority of patients (54.7%) was 2–5 months. Conclusion: We came to the conclusion that partial mole was more common than complete mole .Histopathlogical findings of PHM differ from CHM.The diagnosis of molar pregnancy is helped by histopathological study of products of conception (POC), that can be missed on clinical and ultrasound assessment. As a result, products of conception should be subjected to histological investigation on a regular basis to avoid missing the diagnosis of molar pregnancy.